2021
DOI: 10.1097/prs.0000000000008579
|View full text |Cite
|
Sign up to set email alerts
|

Resorbable Synthetic Ventral Hernia Repair in Contaminated Fields: Outcomes with Poly-4-Hydroxybutyrate Mesh

Abstract: espite years of surgical research, advancements in biomaterial science, and improvement in techniques, ideal mesh selection for ventral hernia repair in the setting of contamination remains controversial. Mesh reinforcement is an integral component of modern hernia surgery, shown to reduce recurrence rates when compared to primary suture repair alone. [1][2][3] With mesh placement, however, comes an increased risk for mesh-related complications. 2 These risks are augmented in patients undergoing contaminated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Our previous study noted an immediate improvement in postoperative AHQ and Hernia-Related Quality-of-Life Survey scores that was maintained over 2 years. 18 On review, our study has found that this trend has continued up to 5 years, with a median follow-up of 4 years. This study's results are consistent with other studies on long-term PROs in hernia repair.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Our previous study noted an immediate improvement in postoperative AHQ and Hernia-Related Quality-of-Life Survey scores that was maintained over 2 years. 18 On review, our study has found that this trend has continued up to 5 years, with a median follow-up of 4 years. This study's results are consistent with other studies on long-term PROs in hernia repair.…”
Section: Discussionmentioning
confidence: 62%
“…study reproduces the methods found in our 2-year follow-up article on P4HB mesh use remain consistent with our results. 18 Adult patients older than 18 years who underwent a single-stage contaminated hernia repair performed by a plastic and reconstructive surgeon at the University of Pennsylvania Health between January 1, 2015, and May 1, 2020 were identified. Patients had follow-up periods ranging from 4 months to 5 years.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that clinical outcomes were evaluated in patients along the entire continuum of Centers for Disease Control (CDC) wound classes ( 33 ) and Ventral Hernia Working Group (VHWG) grades ( 34 , 35 ), ranging from clean cases at low risk of postoperative complications to contaminated/dirty cases at high risk of postoperative complications ( Table 4 ). Systematic reviews ( 59 ), commentaries ( 86 ), and clinical studies of CDC Class I (clean) cases only ( 51 , 65 ) comprised a small number of articles, with the majority of the identified clinical studies describing complex cases with elevated CDC wound class or comorbidities placing patients at high risk of postoperative complications ( n = 13) ( 12 , 30 , 31 , 50 , 52 , 55 , 60 , 62 , 71 , 75 , 76 , 83 , 85 ) or “off-label” use of P4HB mesh to repair ventral/incisional hernias in potentially contaminated or contaminated fields ( n = 15) ( 11 , 53 , 63 , 66 70 , 72 74 , 77 , 78 , 81 , 82 , 84 ). After a thorough evaluation of the clinical studies identified by this scoping review, several major themes emerged, namely: (1) P4HB mesh provides long-term strength at the repair site, leading to acceptable rates of recurrence as compared to higher-risk cohorts and those repaired with non-synthetic biomaterials ( 30 , 31 , 66 , 70 , 75 , 76 ); (2) P4HB mesh performs favorably in contaminated settings where permanent synthetic mesh use may be higher risk or contraindicated, resulting in low incidence of surgical site infection (SSI) ( 70 , 76 , 90 ); and (3) P4HB mesh represents an alternative for ventral/incisional hernia repair relative to biologic meshes and when permanent synthetic mesh complications are taken into consideration ( 30 , 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, P4HB mesh was utilized “off-label” in contaminated hernia repairs, Christopher et al . reported hernia recurrence of 8.3% and SSI of 16.7% at 24 months postimplantation in a patient population with CDC wound class ≥2 and VHWG grade ≥3 hernia repairs ( 72 ). These represent favorable results compared to similar studies involving other types of hernia repair materials.…”
Section: Discussionmentioning
confidence: 99%